A Comparative Study of Anthropometry between Right and Left Hand of Bangladeshi Male Potters - Afrin, Tamanna; Khatun, Monira; Sumi, Sharmin Akhter; Chowdhury, Mahfuza (Bangladesh Journal of Anatomy, 2018)
Context: Anthropometry is a series of systematized measuring techniques that quantitatively express the dimensions of the human body and skeleton. The study was aimed to measure the length, breadth, thickness and span of right and left hand of Bangladeshi male potters. Materials and Methods: One hundred adult Bangladeshi male potters age ranging from 25-55 years were enrolled in this study. Anthropometric measurements, e.g. hand length, breadth, thickness and span were measured with the help of anthropometric equipments such as digital slide calipers and ruler. The measurements were made by same person on both hand for three times. The median value was taken for reliable values. Results: Hand breadth and span were significantly higher (p<0.05) in right hand than left hand of Bangladeshi male potters. Conclusion: In the present study significantly higher value of breadth and span in right hand than left hand was found in male potters of Bangladesh. Bangladesh Journal of Anatomy July 2018, Vol. 16, No. 2, pp. 43-45